Case report: Ultrasound diagnosis of fish bone penetration into the thyroid. Issue 1 (4th December 2019) - Cavelier, Gaëtan; Ostermann, Katharina; Horoi, Mihaela; Huvenne, Raymond; Dequanter, Didier; Rodriguez, Alexandra
Key Clinical Message: Ultrasonography is useful in the diagnosis of foreign body migrations (eg, fish bones) into the soft tissues of the neck. Abstract : Ultrasonography is useful in the diagnosis of foreign body migrations (eg, fish bones) into the soft tissues of the neck.